The mystery of Cabin Island - Dixon, Franklin W. (New York Grosset & Dunlap, 1994)
Joe, Frank, and their friends search the icebound Cabin Island for a missing boy and some stolen medals.
4.0.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Brothers -- Juvenile fiction; Missing children -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction; Mystery and detective stories